The forum of the employer’s domicile in international labour contracts. A note on the judgment of the Social Chamber of the High Court of Justice of Madrid of 17 April 2020 - Belintxon Martin, Unai (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Appeal against the judgment of the Social Court dismissing at first instance the action for dismissal on the ground that the Spanish courts did not have jurisdiction to hear the case of their own motion. Lack of jurisdiction, assessed inadequately, and with clear confusion in the delimitation of forum-ius relations, by the Court of First Instance after analysis of cuban substantive law.